Anti Xa Monitoring during Treatment with Low Molecular Weight Heparin or Danaparoid: Inter-assay Variability - Kitchen, S.; Iampietro, R.; Woolley, A. M.; Preston, F. E. (Thrombosis and Haemostasis, 1999)
If laboratory monitoring of low molecular weight heparin (LMWH) therapy is required the test of choice is the anti Xa activity assay. The relationship between anti Xa results obtained using different techniques is unknown. The aim of the present study was to compare anti Xa results obtained with eight different commercially available anti Xa activity assays (five chromogenic and three clotting based assays) in samples from patients receiving either therapeutic or prophylactic LMWH (enoxaparin or dalteparin) or danaparoid.We have demonstrated that highly significant differences exist between results obtained using different techniques. The mean anti Xa activity in patients receiving treatment or prophylaxis with enoxaparin ranged from 0.28 to 0.64 iu/ml. A similar relationship was present in samples from patients treated with dalteparin, mean anti Xa results ranging from 0.43 to 0.69 iu/ml. The Heptest clotting assay as used here in combination with the Automated Coagulation Laboratory instrument, was associated with lower results than other clotting or chromogenic techniques. In patients receiving danaparoid for heparin induced thrombocytopaenia (HIT) mean results with three clotting based assays were 0.30 to 0.36 u/ml, compared to mean results of 0.47 to 0.65 u/ml for chromogenic assays.Our data clearly indicate that the selection of anti Xa assay method could influence patient management since the dose required to achieve the therapeutic range would differ according to the assay employed. This is particularly important since the frequency of hamorrhagic side effects has been shown by others to be dose dependant, irrespective of the concomitant anti Xa activity results. In danaparoid therapy the clotting assays studied here should not be employed for monitoring without a modified target range, unless it can be demonstrated that the higher doses required to achieve the therapeutic range are safe.